BUSINESS SUCCESS EVALUATION MODEL FOR MSMES: PERFORMANCE AND STRATEGY - Meylin Rahmawati; Retno Dwi Arini; Sulistya Rini Pratiwi; Kartini Kartini; Rizky Agusriyanti Irna (Journal of Applied Economics in Developing Countries, 2025)
The development and growth of Micro, Small, and Medium Enterprises (MSMEs) serve as one of the driving forces of economic growth. The success or failure of an MSME is determined by performance measurement. This study assesses UMKM Amplang Tari's performance using the Balanced Scorecard, focusing on financial, customer, internal business processes, and growth and learning perspectives. The analysis results indicate good cost efficiency, with a Gross Profit Margin of 66% and a Net Profit Margin of 50%, although the Return on Investment (48%) still has room for improvement. A high customer complaint rate (80%) and low customer retention (57%) highlight the need for service improvements. Operationally, high product quality (97%) and on-time delivery (100%) are strengths, but program implementation (67%) requires enhancement. Employee training investment is relatively good (80%), but its impact on innovation needs to be ensured. Recommended improvements include investment optimization, service quality enhancement, strengthening marketing strategies, and product innovation. By implementing these strategies, MSMEs can improve efficiency, customer satisfaction, and competitiveness in the market.